Arctic Marine Resource Governance and Development (Springer Polar Sciences,, 2018)
This book is based on presentations from the Conference 'Arctic Marine Resource Governance' held in Reykjavik Iceland in October 2015. The book is divided into four main themes: 1. Global management and institutions for Arctic marine resources 2. Resource stewards and users: local and indigenous co-management 3. Governance gaps in Arctic marine resource management and 4. Multi-scale, ecosystem-based, Arctic marine resource management'. The ecosystem changes underway in the Arctic region are expected to have significant impacts on living resources in both the short and long run, and current actions and policies adopted over such resource governance will have serious and ultimately irreversible consequences in the near and long terms.